Keluarga Muslim & Generasi Emas STRATEGI KELUARGA MUSLIM DALAM MENCEGAH GANGGUAN KOGNITIF DIGITAL (DIGITAL BRAINROT DAN BRAIN FOG) PADA ANAK: KAJIAN INTEGRATIF HUKUM KELUARGA ISLAM DAN UU PERLINDUNGAN ANAK NO. 35 TAHUN 2014 DALAM MEWUJUDKAN GENERASI EMAS 2045: Mewujudkan Generasi Emas 2045 Melalui Harmonisasi Hukum Keluarga Islam dan UU Perlindungan Anak. - Fitra, Endang Sugiarti (ROSYADA: Islamic Guidance and Counseling, 2025)
The rapid advancement of digital technology has created serious cognitive challenges for children, particularly the emergence of digital brainrot and brain fog. This article analyzes the strategies employed by Muslim families to prevent digital cognitive impairment in children by integrating perspectives from Islamic Family Law and Indonesia’s Child Protection Law No. 35 of 2014 (Articles 20–26). Using a qualitative library research method, this study examines primary and secondary sources from Islamic literature and statutory law. Findings reveal that Muslim families play a central and multidimensional role grounded in the principles of maqashid syari’ah, especially hifdz al-‘aql (protection of intellect) and hifdz al-nasl (protection of progeny). The convergence between Islamic teachings on education (tarbiyah) and parental exemplarity (uswah hasanah), along with legal obligations enshrined in child protection law, forms a comprehensive framework for implementing preventive strategies. These include digital literacy education, adaptive screen-time management, non-digital stimulation, content supervision, parental modeling, and the development of 21st-century soft skills. Holistic application of these strategies is vital to shaping a resilient, intelligent, and morally grounded 2045 Golden Generation amid rapid digital transformation. Keywords: Muslim family, digital cognitive impairment, digital brainrot, brain fog, Islamic Family Law, Child Protection Law No. 35/2014, maqashid sharia, digital literacy, Golden Generation 2045 Abstrak Perkembangan teknologi digital yang pesat menghadirkan tantangan serius bagi kognisi anak, termasuk gejala seperti digital brainrot dan brain fog. Artikel ini mengkaji strategi keluarga Muslim dalam mencegah gangguan kognitif digital melalui pendekatan kualitatif berbasis kajian pustaka. Integrasi antara perspektif Hukum Keluarga Islam dan Undang-Undang Perlindungan Anak No. 35 Tahun 2014 Pasal 20–26 menunjukkan bahwa keluarga memiliki peran sentral dalam perlindungan anak, berlandaskan prinsip maqashid syari’ah, khususnya hifdz al-‘aql dan hifdz al-nasl. Temuan penelitian menekankan pentingnya strategi preventif berupa literasi digital, pengelolaan waktu layar, stimulasi aktivitas non-digital, pengawasan konten, keteladanan orang tua, dan penguatan soft skills anak. Pendekatan holistik ini diposisikan sebagai kontribusi strategis dalam mewujudkan Generasi Emas 2045 yang tangguh secara spiritual, intelektual, dan sosial di tengah tantangan era digital. Kata Kunci: Keluarga Muslim, gangguan kognitif digital, digital brainrot, brain fog, Hukum Keluarga Islam, UU Perlindungan Anak No. 35 Tahun 2014, maqashid syari’ah, literasi digital, Generasi Emas 2045